Sustainable and Eco-Friendly Single- and Multilayer Polyester Foils (Laminates) from Polylactide and Poly(Ethylene 2,5-Furandicarboxylate) - Sandra Paszkiewicz; Izabela Irska; Konrad Walkowiak; Filip Włodarczyk; Magdalena Zdanowicz; Elżbieta Piesowicz; Mateusz Barczewski (Molecules)
Packaging materials mainly serve the function of protecting products. The most common representative of this group is poly(ethylene terephthalate) (PET), which is not biodegradable and therefore, its waste might be burdensome to the environment. Thus, this work aims to develop outlines for obtaining polyester-based systems, preferably biobased ones, intended for the packaging industry and their detailed characterization. The obtained multilayer systems based on two biobased thermoplastic polyesters, i.e., poly(ethylene 2,5-furandicarboxylate) (PEF) and the “double green” polylactide (PLA), were subjected to various analyses, i.e., UV-Vis spectrophotometry, microscopic evaluation, tensile tests, differential scanning calorimetry (DSC), oxygen transmission rate (OTR), water absorption tests, surface analyses, and biofilm formation. The best possible arrangement was selected in terms of the packaging industry. It was proven that the elastic modulus was significantly higher for multilayer systems, whilst higher-strength parameters were observed for PLA single foils. Regardless of thickness, PLA and PEF foils exhibit similar absorption values in cold water. Moreover, PEF foils demonstrated significantly better barrier properties towards oxygen gas compared to PLA foils of the same thickness. However, a multilayer system composed of two PLA foils with a single inner PEF foil had an OTR value only slightly higher than that of the PEF foil alone. PEF was also found to be a material that exhibited a limited formation of bacterial biofilm, particularly strains of S. aureus and E. coli. All of the above findings clearly confirm the sensibility of the research topic undertaken in this work on the application of biobased thermoplastic polyesters in the packaging industry.